Long term post-surgical hypoparathyroidism (PoSH) – time to revise the definition?. (1st March 2022) - Arshad, Muhammad Fahad; Dhami, Amardass; Quarrell, Gillian; Balasubramanian, Saba P
Abstract: Aims: Post-surgical hypoparathyroidism (PoSH) is common after thyroidectomy. Most cases recover within 6 months. If persistent beyond 6 months, PoSH is considered to be 'long term' as per BAETS guidelines. The aim of the study is to determine the frequency of late recovery in this group and factors that can predict this. Methods: Adult patients undergoing total or completion thyroidectomy between 2009–18 were included in this cohort prospective observational study. Records of patients who met certain inclusion criteria (started on calcium or activated vitamin D, or day 1 adjusted calcium <2.1 mmol/L, or day 1 PTH <1.6 pmol/L) were reviewed to identify those with PoSH at 6 months. Demographic, biochemical, surgical, pathological and clinical follow-up data is described and analysed. Results: Out of 911 patients undergoing thyroidectomy, 270 met the inclusion criteria. Of these, 192 were started on supplements and 138 (71.9%) recovered within six months. Of the remaining 54 patients, 19 (47.5%) had remission and 21 had ongoing PoSH beyond 3 years follow-up (median follow-up 4.5 years). All of those recovered had a PTH of ≥1.6 pmol/L at/beyond 6 months. There was no difference in age, gender, diagnosis, extent of surgery, or calcium levels between the two groups. Conclusions: Recovery from PoSH is common beyond 6 months, raising the question of whether the 6-month threshold is appropriate. In patients with a PTH level of ≥1.6 pmol/L at/after 6 months, the chances of recovery are high (60%).